Association between Vitamin B12 and Risk of Gastric Cancer: A Systematic Review and Meta-Analysis of Epidemiological Studies. (13th August 2022) - He, Jianbo; Fu, Hongjuan; Li, Cancan; Deng, Zhihui; Chang, Hui
Abstract: Epidemiological studies focusing on the association between vitamin B12 and gastric cancer risk reported inconsistent findings. We conducted a systematic review and meta-analysis to assess the relationship. PubMed (Medline), Web of science and EMBASE databases were systematically searched. A total of nine studies involving 3, 494 cases of with gastric cancer and 611, 638 participants were included. The result showed that there is no significant association between vitamin B12 intake and the risk of gastric cancer (OR = 0.88, 95% CI: 0.69-1.12, P = 0.303). Nevertheless, high intake of vitamin B12 might decrease the risk of gastric cancer in Helicobacter pylori ( Hp )-negative people (OR = 0.83, 95% CI: 0.62-0.99, P = 0.044), but increase the cancer risk in Hp -positive populations (OR = 1.66, 95% CI: 1.27-2.16, P = 10 −4 ). Additionally, further analysis indicated that excessive vitamin B12 might increase the risk of non-cardia gastric cancer (OR = 1.15, 95% CI: 1.01-1.33, P = 0.006). A negative association between vitamin B12 intake and gastric cancer risk was found in nonsmokers (OR = 0.83, 95% CI: 0.71-0.96, P = 0.012) but not in smokers (OR = 1.08, 95% CI: 0.71-1.47, P = 0.619). In conclusion, although we found no convincing evidence that vitamin B12 intake is associated with the risk of gastric cancer, it is important to maintain the relative stability of vitamin B12 for people with Hp infection.